Mental rehearsal improves passing skill and stress resilience in rugby players - Beaven, C. M.; Kilduff, L. P.; Cook, C. J. (International Journal of Sports Physiology and Performance, 2023)
Purpose: Mental rehearsal is commonly employed, with positive visualization proposed to enhance complex skill performance. Additionally, video stimulus has been associated with enhanced kinesthetic sensations and rapid hormone fluctuations that may contribute to enhancing mental rehearsal and the conscious and unconscious emotional state for skill execution. Here, we assessed the impact of a 15-minute mental rehearsal intervention on rugby-specific tasks and the associated hormone profile.